Nutritional Evaluation of Sweet Orange (Citrus sinensis) Fruit Peel as a Feed Resource in Broiler Production - Agu, P.N.; Oluremi, O.I.A.; Tuleun, C.D. (International Journal of Poultry Science, 2010)
A study was conducted with broiler chicks to evaluate the nutritional potential of Sweet orange fruit (Citrus sinensis) peel as a feed resource. Sweet orange peels were sun dried, milled and used as a dietary substitute for maize. Six experimental diets coded as M100P0, M90P10, M80P20, M70P30, M60P40 and M50P50 were compounded such that Sweet Orange Peel Meal (SOPM) substituted maize at levels of 0, 10, 20, 30, 40 and 50%, respectively in broiler starter and finisher diets. One hundred and eighty (180) day-old Anak titan chicks were randomly divided into six groups and one of each was allotted to a diet of three replicates. The birds which were raised in deep litter pens for sixty-three days were fed ad libitum and had access to fresh cool drinking water daily. Performance data: feed intake, water consumption, body weight, Body Weight Gain (BWG), Feed Conversion Ratio (FCR) were collected during the feeding trial and carcass evaluation was done at the termination of the trial. In both starter and finisher phases, the diets had no effect (p>0.05) on feed intake, water consumption, body BWG and FCR but had significant effect (p<0.01) on the body weight of broilers as the level of the SOPM increased from 0-50%. There was a significant decrease in body weight at SOPM level higher than 20%. Experimental diets had highly significant effect (p<0.001) on dressing percent, drumstick and wing from 30% level of SOPM while other carcass cuts: thigh, breast, back, neck and shoulder were statistically the same (p>0.05) among the dietary groups. The diets had no effect (p>0.05) on kidney, liver, heart, spleen, gall bladder and lung but had significant effect (p<0.01) on proventriculus and gizzard as the SOPM level increased. The organs were normal and there were no observable adverse effects on the health of broilers. SOPM can be a dietary substitute for maize up to 20% level in the diet for broiler.